2009
DOI: 10.1021/jp905748j
|View full text |Cite
|
Sign up to set email alerts
|

Sintering, Coalescence, and Compositional Changes of Hydrogen-Terminated Silicon Nanoparticles as a Function of Temperature

Abstract: Sintering, coalescence, and compositional changes of hydrogen-terminated, crystalline silicon nanoparticles were examined as a function of temperature. Monodisperse aerosol particles ∼5 nm in diameter were synthesized by gas-to-particle conversion in a plasma reactor and then immediately heated as they flowed through a tube furnace. Particles were also collected as powders and then heated in other apparatuses. Structure and size changes were characterized by X-ray diffraction (XRD) and transmission electron mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 50 publications
1
21
1
Order By: Relevance
“…Since surface hydrogen desorbs from different surface groups at different temperatures, the surface hydrogen coverage may be used as an empirical measure of the particle temperature history. Holm and Roberts showed that surface hydrogen first desorbs from SiH 3 groups between 400–500 °C, while it persists to temperatures of up to 650 °C in SiH 2 and more than 700 °C in SiH groups 25. The increased SiH 3 coverage with increased hydrogen injection may thus indicate faster cooling of the SiNCs emerging the synthesis plasma, due to the higher thermal conductivity of hydrogen compared to that of argon. Improved SiNC hydrogen coverage due to an increased flux of atomic hydrogen species.…”
Section: Resultsmentioning
confidence: 99%
“…Since surface hydrogen desorbs from different surface groups at different temperatures, the surface hydrogen coverage may be used as an empirical measure of the particle temperature history. Holm and Roberts showed that surface hydrogen first desorbs from SiH 3 groups between 400–500 °C, while it persists to temperatures of up to 650 °C in SiH 2 and more than 700 °C in SiH groups 25. The increased SiH 3 coverage with increased hydrogen injection may thus indicate faster cooling of the SiNCs emerging the synthesis plasma, due to the higher thermal conductivity of hydrogen compared to that of argon. Improved SiNC hydrogen coverage due to an increased flux of atomic hydrogen species.…”
Section: Resultsmentioning
confidence: 99%
“…The drop of SiH 3 groups occurs most drastically at around 400−500 °C (Figure 5e), which is consistent with the desorption temperatures observed by Holm and Roberts for hydrogen-terminated, plasma-synthesized Si NCs. 47 The surfaces of Si NCs synthesized from a nonthermal plasma consist of silicon monohydride (SiH), dihydride (SiH 2 ), and trihydride (SiH 3 ) groups. In a previous study, it was observed that PLQY of plasma-synthesized Si NCs can be improved by heating them to 160 °C in mesitylene for an hour.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Therefore, the 1032 °C temperature is a critical point (i.e., critical sintering temperature, T CS ) at which reaction type changes from endothermic to exothermic. After 805 °C, desorption and absorption of oxygen occur cyclically 25 up to the melting point of Si (i.e., 1412 °C). As the melting point of SiNW is lower than the bulk-Si, the cyclic absorption and desorption of oxygen may last for a much lesser sintering temperature than the bulk-Si.…”
Section: Resultsmentioning
confidence: 99%
“…10 (c). Holm et al 25 reported that sintering of Si nanoparticles merges differently oriented neighboring SiNCs at 750 °C (Fig. 10 (e)), whereas the polycrystalline NP transforms to single-crystalline at 1000 °C.…”
Section: Discussionmentioning
confidence: 99%